PENGARUH AUDITOR INTERNAL DAN KEBIJAKAN MANAJEMEN TERHADAP EFEKTIVITAS KEAMANAN SIBER - sherina sherina; Deni Darmawati (Jurnal Ekonomi Trisakti, 2022)
This study aims to analyze and examine the effect of internal auditor certification, risk assessment, the role of senior management, the strategies adopted by senior management and technical measures on the effectiveness of cybersecurity. The population of this research is internal auditors who have experience in cyber security and information technology. The sample of this study was 70 respondents who were obtained from the Lemeshow formula with the snowball sampling method. The results of this study indicate that internal auditor certification, risk assessment, the role of senior management, strategies adopted by senior management and technical measures have a positive effect on cybersecurity effectiveness.